Characterization of Physico-Chemical Levels of β-Carotene and Antioxidant Activity in Dried Carrot Dregs Powder - Farida Nuraeni; Siti Warnasih; Vevi Hikmafitri Rizali (Universitas Pakuan, 2021)
Carrots contain many nutrients needed by the human body, especially as a source of vitamin A. Carrot pulp is a byproduct of the carrot juice process. The utilization of carrot dregs in household waste as food is still low. To increase added value, carrot dregs can be used as an additional ingredient as flour. The process of making dry carrot dregs uses the oven method with variations in drying temperature and time spent drying. The drying temperatures applied in this study were 40◦C, 50◦C, 60◦C and 70◦C with time variations of 17, 22, 27, 32 hours. Physicochemical testing includes yield levels, protein content test using the Kjeldahl method, water content test, ash content test, β-carotene content test using HPLC, vitamin A test, DPPH method antioxidant activity test and organoleptic test. Organoleptic tests in this study include texture, color and smell. The best results were obtained from the assessment of the organoleptic test which had the highest average value, namely carrot dregs dried at a temperature of 50 32C for 32 hours with a value of 6.0, which means the product was rather favored by the panelists.Carrot dregs dried at 50◦C for 32 hours had a yield rate of 19.30%, a moisture content of 4.41%, an ash content of 4.91%, a protein content of 4.07%, the antioxidant test had% inhibition of 661.30 ppm classified as a weak antioxidant. In the dried carrot dregs powder it still contains β-carotene although the level is only 1.92 mg with a vitamin level of 3187.2 IU. This shows that carrot dregs still contain β-carotene and vitamins even though the levels are not high and can function as an antioxidant inhibitor.